2020
DOI: 10.1158/1078-0432.ccr-19-2706
|View full text |Cite
|
Sign up to set email alerts
|

RABL6A Is an Essential Driver of MPNSTs that Negatively Regulates the RB1 Pathway and Sensitizes Tumor Cells to CDK4/6 Inhibitors

Abstract: Purpose: Malignant peripheral nerve sheath tumors (MPNSTs) are deadly sarcomas that lack effective therapies. In most MPNSTs, the retinoblastoma (RB1) tumor suppressor is disabled by hyperactivation of cyclin dependent kinases (CDKs), commonly through loss of CDK inhibitory proteins such as p27(Kip1). RABL6A is an inhibitor of RB1 whose role in MPNSTs is unknown. To gain insight into MPNST development and establish new treatment options, we investigated RABL6A-RB1 signaling and CDK inhibitor-based therapy in M… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
67
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(86 citation statements)
references
References 83 publications
(138 reference statements)
3
67
0
Order By: Relevance
“…One study showed that cytoplasmic p27 KIP1 localization correlates with increased nuclear cyclin E1 expression and poor prognosis in MPNST patients [83]. Most recently, immunohistochemical analyses of patient matched PNFs and MPNSTs revealed dramatic upregulation of an oncogenic GTPase, RABL6A, in MPNSTs [84]. RABL6A is a newly recognized negative regulator of RB1 and p53 signaling [85][86][87].…”
Section: Malignant Peripheral Nerve Sheath Tumors (Mpnsts)mentioning
confidence: 99%
See 2 more Smart Citations
“…One study showed that cytoplasmic p27 KIP1 localization correlates with increased nuclear cyclin E1 expression and poor prognosis in MPNST patients [83]. Most recently, immunohistochemical analyses of patient matched PNFs and MPNSTs revealed dramatic upregulation of an oncogenic GTPase, RABL6A, in MPNSTs [84]. RABL6A is a newly recognized negative regulator of RB1 and p53 signaling [85][86][87].…”
Section: Malignant Peripheral Nerve Sheath Tumors (Mpnsts)mentioning
confidence: 99%
“…RABL6A is a newly recognized negative regulator of RB1 and p53 signaling [85][86][87]. In MPNSTs, RABL6A was found to promote MPNST pathogenesis, in part, through its downregulation of p27 KIP1 , activation of CDKs, and inhibition of RB1 [84].…”
Section: Malignant Peripheral Nerve Sheath Tumors (Mpnsts)mentioning
confidence: 99%
See 1 more Smart Citation
“…These investigations have confirmed or supplemented the genomic data by assaying downstream pathway effects in human MPNST. Several studies have broadly analyzed gene expression in human MPNST samples using microarray or RNAseq approaches [ 48 , 88 ]; these data can be examined in relation to known genetic changes to generate additional hypotheses for effects on downstream signaling pathways. Recent work compared gene expression in multiple functional pathways across pNF, ANF/ANNUBP, and MPNST and found that some ANNUBP share signaling pathway characteristics that more closely resemble pNF (e.g., ERK/MAPK) and others (e.g., AKT/mTOR) are more similar to MPNST [ 88 ].…”
Section: Beyond Genomics: the State Of Understanding Mpnst Transcrmentioning
confidence: 99%
“…Several studies have broadly analyzed gene expression in human MPNST samples using microarray or RNAseq approaches [ 48 , 88 ]; these data can be examined in relation to known genetic changes to generate additional hypotheses for effects on downstream signaling pathways. Recent work compared gene expression in multiple functional pathways across pNF, ANF/ANNUBP, and MPNST and found that some ANNUBP share signaling pathway characteristics that more closely resemble pNF (e.g., ERK/MAPK) and others (e.g., AKT/mTOR) are more similar to MPNST [ 88 ]. Phospho-proteome arrays may be used to investigate kinase signaling in relation to various genomic alterations or therapeutic interventions in MPNST; to date this has primarily been used in MPNST cell lines or animal models (see article by Grit et al in this Special Issue on Genomics and Models of Nerve Sheath Tumors) [ 89 ].…”
Section: Beyond Genomics: the State Of Understanding Mpnst Transcrmentioning
confidence: 99%